DIVERSIFIKASI PENDAPATAN, RISIKO KREDIT, LOAN TO DEPOSIT RATIO, RISK AVERSION DAN NET INTEREST MARGIN - Irvan Zulfikar, Faizal; Demi Pengestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2018)
Net Interest Margin shows an upward trend in 2015 and 2016, but the increase hasn’t been able exceed Net Interest Margin in 2012. This indicates that the bank's performance in obtaining NIM hasn’t been as optimal as 2012. This research aims to analyze the influence of income diversification, credit risk, loan to deposit ratio, and risk aversion to Net Interest Margin (NIM) of conventional bank listed in IDX during the periods 2012 - 2016. Income diversification is measured by NII ratio, credit risk is measured by NPL ratio, loan to deposit ratio is measured by LDR, and risk aversion is measured by CAR. This research also using bank size and BOPO (efficiency ratio) as control variable.The data studied were obtained through non-participant observation method by directly quoting financial and banking data. The data sources used in this study came from Bloomberg and OJK. The sampling technique used was purposive sampling. Based on the criteria determined, it will get 36 conventional banks. Data analysis in this study used multiple linear regression analysis, which had previously passed the classical assumption test.Result of this research show that income diversification, credit risk, loan to deposit ratio, and risk aversion have positive and significance effect to net interest margin.